Effect of ethoxylated bisEMA on water sorption of 3D-printed splints - Dr Lippo Lassila; Dr Junichiro Wada; Prof Pekka Vallittu; Dr Sufyan Garoushi (Elsevier, 2023)
Aim or Purpose: A significant loss or gain in weight of splint material would indicate a possible risk of a material to stand up to oral exposure. bisEMA is commonly used monomer in 3D-printed splints. However, bisEMA is general name for group of different monomers having various chainlength of ethoxylated bisEMA. In this study effect of chain length of ethoxylated bisEMA was evaluated on water sorption on 3D-printed splint material. Materials and Methods: 2-different ethoxylated bisEMA (chain of short n+m=4 BE-s or long n+m 10, BE-l) was used to make 7 different mixture of resin. Total wt% of bisEMA was 80% and it was mixed with 20 wt% UDMA. As an initiator TPO 2% was used. Ratio of BE-s and BE-l was varied as follows wt% (80-0,60-20,50-30,40-40,30-50,20-60,0-80). Bar shaped specimen (8/group,3 × 10 × 60mm) were 3D-printed using Asiga MAX (Scheu Dental) followed stroboscopic post curing (Otoflash,2 × 2000). Specimens were water stored for 31 days in 37°C and each specimen were weighted 1,2,3,5,7,124,21,28,31 days. After water immersion, specimens were dehydrated at desiccator at 60°C until no weight change occurred anymore. Data was analysed using ANOVA(p<0.05). Results: When concentration of long chain bisEMA at resin mixture was increased from 0% to 80%, water sorption was increased also from 1.31% to 4.02% (p<0.05) similarly. Solubility was not affected by ratio of long and short bisEMA concentration (p>0.05). Interestingly water saturation with long chain bisEMA occurred faster than with short chain bisEMA. Conclusions: When optimising 3D splint materials for clinical use, monomer structure of bisEMA plays significant role on water sorption.